Hubungan Kepatuhan Menggunakan Alat Pelindung Diri dengan Imunoglobulin E (IgE) Total pada Pekerja Industri Textil - Bintang Aulia Nur’aini; Hari Saktiningsih (Jurnal Sains dan Kesehatan, 2026)
Chemical exposure during the dyeing process in the Textile industry has the potential to cause health problems, particularly allergic reactions mediated by Immunoglobulin E (IgE). Non-compliance with the use of Personal Protective Equipment (PPE) may increase the risk of chemical exposure through inhalation and skin contact, thereby triggering an allergic immune response characterized by elevated total IgE levels in the blood. This study aimed to determine the relationship between compliance with the use of Personal Protective Equipment (PPE) and total Immunoglobulin E (IgE) levels among Textile industry workers. This research was an analytic observational study with a cross-sectional design. The sample consisted of 15 Textile industry workers who met the inclusion and exclusion criteria, selected using purposive sampling technique. Data on PPE compliance were obtained through questionnaires and interviews, while total IgE levels were measured using the Electrochemiluminescence Immunoassay (ECLIA) method. The relationship analysis was conducted using Fisher’s Exact test. The results showed a significant relationship between PPE compliance and total IgE levels (p<0.05). It can be concluded that there is a significant association between compliance with the use of Personal Protective Equipment and total Immunoglobulin E (IgE) levels among Textile industry workers.